2014
DOI: 10.4172/2161-0460.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Positive Spherical Deposits (SPD) Detected in the Molecular Layer of Hippocampal Dentate Gyrus of Dementia, Down’s Syndrome ,and Schizophrenia

Abstract: Lectins are proteins which specifically bind (or crosslink) carbohydrates. Recent studies have shown the importance of glycosylation in pathogenesis of diseases. Lectin-positive spherical deposits (SPD), 3-10 micron in diameter, have been detected in the molecular layer of dentate gyrus of hippocampus in dementia, Down's syndrome, and schizophrenia. In schizophrenia, SPD was observed without exception, regardless of having history of pharmacotherapy. Multi-labeling histochemical methods, revealed that single s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous studies in schizophrenia brain have identified abnormalities of multiple glycosylation pathways (Bauer et al, 2010; Berretta, 2012; Berretta et al, 2015; Ikemoto, 2014; Mueller et al, 2014; Narayan et al, 2009; Pantazopoulos et al, 2013; Stanta et al, 2010; Telford et al, 2012; Tucholski et al, 2013b, 2013a) and dysregulated expression of glycosylation enzymes has been proposed as a possible mechanism underlying these deficits. Our current report builds on the prior finding of altered transcript levels of CAzymes in schizophrenia cortex by assessing the protein expression of a subset of these, fucosyltransferases and fucosidases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in schizophrenia brain have identified abnormalities of multiple glycosylation pathways (Bauer et al, 2010; Berretta, 2012; Berretta et al, 2015; Ikemoto, 2014; Mueller et al, 2014; Narayan et al, 2009; Pantazopoulos et al, 2013; Stanta et al, 2010; Telford et al, 2012; Tucholski et al, 2013b, 2013a) and dysregulated expression of glycosylation enzymes has been proposed as a possible mechanism underlying these deficits. Our current report builds on the prior finding of altered transcript levels of CAzymes in schizophrenia cortex by assessing the protein expression of a subset of these, fucosyltransferases and fucosidases.…”
Section: Discussionmentioning
confidence: 99%
“…Several neurotransmitter receptors, transporters, and associated molecules with atypical patterns of glycosylation have been identified in schizophrenia brain (Barbeau et al, 1995;Bauer et al, 2010;Gilabert-Juan et al, 2012;Mueller et al, 2014;Tucholski et al, 2013bTucholski et al, , 2013aVarea et al, 2012). Transcript-level studies have found mRNA levels of some glycosylation enzymes altered in this illness, and abnormal expression of specific glycan structures and monosaccharides in patient cerebrospinal fluid and blood serum have been reported (Ikemoto, 2014;Maguire et al, 1997;McAuley et al, 2012;Mueller et al, 2018;Narayan et al, 2009;Stanta et al, 2010). Previous glycobiology research in schizophrenia has focused on abnormal glycan expression and altered glycosylation of substrate proteins, while mechanisms which underlie glycosylation defects have not been as extensively explored.…”
mentioning
confidence: 99%
“…Our lab has previously hypothesized that deficits of neurotransmission are not only due to abnormal expression of neurotransmitterassociated molecules, but may also result from abnormal receptor targeting and subcellular localization (Hammond et al, 2011;Mueller et al, 2015). Glycosylation is a PTM that plays a pivotal role in protein trafficking and subcellular targeting and has been shown in multiple studies to be abnormal in schizophrenia (Berretta, 2012;Ikemoto, 2014;Mueller et al, 2014;Narayan et al, 2009;Pantazopoulos et al, 2013;Sato and Kitajima, 2013;Stanta et al, 2010;Tucholski et al, 2013bTucholski et al, , 2013a.…”
mentioning
confidence: 99%